Application of EMG-signal phase portraits for differentiation of musculoskeletal system diseases - Zhemchuzhkina, Tatyana V.; Zlepko, Sergii M.; Nosova, Tatyana V.; Semenets, Valerii V.; Kirichek, Oleksii V.; Maciejewski, Marcin; Ormanbekova, Ainur (Wilga, Poland, 2019)
This article examines the dependence of the set of parameters of the phase portrait of an EMG signal on age, sex, and the diagnosis of the examined by methods of statistical analysis. the work is carried out on the basis of the results of the examination in four groups of patients: practically healthy without complaints; conditionally healthy with complaints of back pain; vertebral patients; patients with scoliosis. the studies were conducted in collaboration with the laboratory of pathophysiology of the Sitenko institute of spine and joint pathology Ukrainian academy of medical sciences. the study was performed with 102 people of both sexes aged 18 to 76 were examined. statistical processing of samples to identify statistically significant correlations of the parameters of the phase portrait of the EMG signal with the age and sex of the subject was conducted. statistically significant differences were not found. statistical processing of the sample to identify statistically significant correlations between the group to which the patient belongs, and each indicator of the phase portrait was conducted. the groups of practically healthy patients without complaints and conditionally healthy patients with complaints of back pain are not statistically significantly different for each parameter of the phase portrait. However, between patients without pathologies, vertebral patients and patients with scoliosis, a statistically significant difference was found for seven parameters of the phase portrait. The perspective of the work is the construction of models for classifying patients according to the parameters of phase portraits of surface electromyography data.
Zhemchuzhkina Tatyana V. Application of EMG-signal phase portraits for differentiation of musculoskeletal system diseases / Tatyana V. Zhemchuzhkina, Sergii M. Zlepko, Tatyana V. Nosova, Valerii V.Semenets, Oleksii V. Kirichek, Marcin Maciejewski, Ainur Ormanbekova // Proceedings of the SPIE. - Wilga, Poland, 2019. – Vol. 11176. – 6 р.
Keywords: muscle; statistics; phase portrait; electromyogram; ellipse